Tolerance of guava rootstocks under salt stress - Francisco V. da S. Sá; Reginaldo G. Nobre; Luderlândio de A. Silva; Rômulo C. L. Moreira; Emanoela P. de Paiva; Fernanda A. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the tolerance of guava rootstocks under salt stress in the initial development stage. The experiment was conducted in a greenhouse in a randomized block design in a 5 x 3 factorial, consisting of five levels of irrigation water salinity (0.6, 1.2, 1.8, 2.4 and 3.0 dS m-1) and three guava rootstocks (‘Crioula’, ‘Paluma’ and ‘Ogawa’), with four replicates and four plants per replicate. Emergence, growth and phytomass accumulation were evaluated 30 days after sowing. Increased salinity restricts guava emergence, growth and phytomass accumulation, and the most drastic effects occur at levels higher than 1.8 dS m-1. The cultivar ‘Crioula’ is more tolerant to salinity in relation to ‘Paluma’ and ‘Ogawa’, and can be indicated as rootstock.